Molecular Properties Important for Inhaled Anesthetic Action on Human 5-HT(3A) Receptors - Stevens, Renna J. N. (Anesth Analg, 2005)
Although inhaled anesthetics have diverse effects on 5-hydroxytryptamine type 3 (5-HT(3A)) receptors, the mechanism accounting for this diversity is not understood. Studies have shown that modulation of 5-HT(3A) receptor currents by n-alcohols depends on molecular volume, suggesting that steric interactions between n-alcohols and their binding sites define their action on this receptor. Electrostatic interactions also play an important role in anesthetic action on other ligand-gated receptors. We aimed to determine the contribution of molecular volume and electrostatics in defining volatile anesthetic actions on 5-HT(3A) receptors. Human 5-HT(3A) receptors were expressed in, and recorded from, Xenopus oocytes using the two-electrode voltage-clamp technique. The effects of a range of volatile anesthetics, n-alcohols, and nonhalogenated alkanes on submaximal serotonin-evoked peak currents, and full serotonin concentration-response curves were defined. Volatile anesthetics and n-alcohols, but not alkanes, smaller than 0.120 nm(3) enhanced submaximal serotonin-evoked peak currents whereas all larger agents reduced currents. Most compounds tested inhibited maximal serotonin-evoked peak currents to varying degrees. However, only agents smaller than 0.120 nm(3) shifted the 5-HT(3A) receptor’s serotonin concentration-response curve to the left, whereas larger anesthetics shifted them to the right. Modulation of human 5-HT(3A)-mediated currents by volatile anesthetics exhibits a dependence on molecular volume consistent with the n-alcohols, suggesting that both classes of agents may enhance 5-HT(3A) receptor function via the same mechanism. Furthermore, the enhancing but not inhibiting effects of anesthetic compounds on 5-HT(3A) receptor currents are modulated by electrostatic interactions.